A phenomenological study on the lives of low-income working mothers during the COVID-19 pandemic - Baharuddin, Noor Najwa; Hussin, Ruhaya; Tajuddin, Nor Azlin (IIUM Press, 2023)
This study explores the lived experience of low-income (B40) working mothers in Klang Valley during the COVID-19 pandemic. It sheds light on their mental health struggles and unexpected silver linings. Eight participants were selected through purposive and snowball sampling. A seven-day diary-writing exercise followed by individual interviews was conducted. Data analysis is based on descriptive phenomenology, allowing in-depth exploration of participants' experiences. Three main themes emerged from the analysis: (1) Multitasking is too taxing, highlighting the intensified role conflict faced by some mothers; (2) Struggling to regulate emotions, revealing the guilt and emotional challenges these mothers experienced as they juggled multiple roles; and (3) The upside of COVID-19, demonstrating how some participants found unexpected benefits in increased family bonding during lockdowns. In sum, low-income working mothers faced significant mental health challenges during the COVID-19 pandemic, exacerbated by their unique circumstances. The findings underscore the importance of recognising their struggles and the need for interventions that promote their mental well-being. Additionally, providing training in emotional resilience and self-regulation could prove beneficial. This study contributes to the understanding of the nuanced experiences of low-income working mothers and calls for continued attention to their mental health needs, particularly in times of crisis.